On the efficiency of codeshare contracts between airlines: is double marginalization eliminated? - Gayle, Philip G. (My University, 2013)
Previous research has suggested that codeshare agreements eliminate double marginalization that exists when unaffiliated airlines independently determine the price for different segments of an interline trip. Using a structural econometric model, this paper investigates whether codeshare contracts do eliminate double marginalization. The results suggest that both upstream and downstream margins persist when the operating carrier of a codeshare product also offers competing single-carrier product(s) in the concerned market. Furthermore, counterfactual simulations from the model suggest that efficient pricing of these codeshare products would lower their price, and yield nontrivial increases in consumer welfare.
Keywords: Double marginalization; Airlines; Codeshare contracts